2020
DOI: 10.3390/cancers12102897
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography in Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare neuroendocrine skin malignancy usually arising as a nonspecific nodule on sun-exposed areas of the head and neck. Given the poor prognosis of this aggressive tumor, assessment of disease burden in pre- and post-treatment care may ensure an optimal management with significant implications for patient surveillance and prognosis. Although imaging has established its role in locally advanced or distant metastatic MCC, a standard imaging algorithm is yet to be determined and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
(161 reference statements)
0
11
0
1
Order By: Relevance
“…71 The role of 18F-FDG PET/CT in the management of the locoregional MCC is limited, but current evidence suggests a possible significant role even in localized MCC cases. 72 Within Delphi participants there was a very high consensus and agreement regarding the need for evaluation of sentinel lymph nodes and the need for clinical radiological follow-up in patients undergoing curative treatments.…”
Section: Open Accessmentioning
confidence: 99%
“…71 The role of 18F-FDG PET/CT in the management of the locoregional MCC is limited, but current evidence suggests a possible significant role even in localized MCC cases. 72 Within Delphi participants there was a very high consensus and agreement regarding the need for evaluation of sentinel lymph nodes and the need for clinical radiological follow-up in patients undergoing curative treatments.…”
Section: Open Accessmentioning
confidence: 99%
“…However, a recent retrospective analysis revealed that of 492 patients with no signs or symptoms of regional or distant spread, 65 (13%) were upstaged by diagnostic imaging (CT, MRI, or FDG-PET-CT) with consequences for treatment [ 36 ]. Confirmative data are provided by a literature review on the role of FDG-PET-CT [ 37 ]. In addition, or as an alternative to PET-CT, ultrasound with fine needle cytology can be considered for the evaluation of regional lymph nodes [ 38 , 39 ].…”
Section: Diagnostics and Stagingmentioning
confidence: 99%
“…However, guidelines and reviews concur that the preferred diagnostic method for assessment of lymph node status is sentinel lymph node biopsy (SLNB) [ 18 , 35 , 37 , 38 , 39 , 40 ]. In 25–45% of patients clinically staged N0, SLNB demonstrated lymph node metastases with the majority of studies indicating a number close to 30% [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Diagnostics and Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In most reports, the glucose analog 18 F-fluorodeoxyglucose ( 18 F-FDG) was used as a radiotracer, although 68 Ga-labeled somatostatin analogs have been employed as well as 6-fluoro-( 18 F)-L-3,4-dihydroxyphenylalanine ( 18 F-DOPA). Nevertheless, currently, PET-CT is still inferior in sensitivity in detecting the early stages of MCC in comparison to sentinel lymph node biopsy, but an important role for 18 F-FDG PET/CT in the staging of MCC is expected [21,22]. Merkel cell carcinoma histological features with its typical immunohistochemical profile (CK20+, CKAE1/AE3+, Chromogranin A+, SATB2+, and TTF-1-), focal necrosis (see: asterisk), and brisk mitotic activity (see: arrows).…”
Section: Introductionmentioning
confidence: 99%